The Effect of Promotion Strategy and Quality of Service on Consumer Purchase Decisions at Tendean Branch Mcdonald's In Jakarta Selatan - Kasmad Kasmad (Jurnal Ad'ministrare, 2022)
This study aims to determine the effect of promotional strategies and service quality on consumer purchasing decisions at McDonald's Tendean Branch in South Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that Promotion Strategy has a significant effect on purchasing decisions by 37.0%, hypothesis testing is obtained t count > t table or (7,580 > 1,989). Service quality has a significant effect on purchasing decisions by 50.9%, hypothesis testing is obtained t count > t table or (10.088 > 1.989). Promotion strategy and service quality simultaneously have a significant effect on purchasing decisions with the regression equation Y = 9.146 + 0.257X1 + 0.527X2 and the contribution of the influence is 56.8%, hypothesis testing is obtained F count > F table or (63.656 > 2.770).